Towards a Utility Framework for Enterprise Business Intelligence Mashups - Ahmed, Sabbir (Université d'Ottawa / University of Ottawa, 2014)
Organizations today are adopting business intelligence (BI) systems at a fast pace with the expectation that these systems will help them make better business decisions and improve their performance. But with the ever changing industry dynamics and variable business needs of end-users, the BI requirements of organizations are also getting unpredictable and increasingly harder to deliver by the service providers. Additionally, the advancement of web 2.0 & enterprise 2.0 technologies has opened up more possibilities for the development of user-centric innovative business applications. Enterprise BI Mashups are a specific breed of such technologies that have the potential to empower end-users with self-service capabilities and facilitate problem-solving in ad-hoc situational BI scenarios. This research project attempts to explore the current landscape of Business Intelligence (BI) Mashups and to identify gaps in technology with respect to user requirements and corporate objectives. Through an empirical investigation of BI mashups use cases, specific issues and challenges associated with the use of mashups in BI have been ascertained. Working in collaboration with IBM Cognos, we have formulated a taxonomy and utility framework for Enterprise BI Mashups. The formulated taxonomy provides a basic framework for understanding the domain of BI mashups and is aimed to aid application development initiatives for creating BI mashups toolkits. The utility framework draws upon real-world use cases for BI Mashups as well as pertinent software design patterns that can facilitate the development of BI mashup tools and services. These frameworks are expected to advance an understanding of business process requirements that can be satisfied through the use of Enterprise BI Mashups, and also aid in the development of mashup toolkits targeted at BI end-users.
Keywords: enterprise mashups; business intelligence; BI mashups; self-service; end-user development; web 2.0; enterprise 2.0; situational applications